Medical-biological studies of artificial biomaterials for orthopaedics and traumatology - Malyshkina, Svitlana; Dedukh, Ninel (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2010)
On the basis of their own researches and scientific information, the authors present a methodological approach to the medical-biological assessment of artificial biomaterials for orthopaedics, traumatology and dentistry with use of a complex of methods of examination in vitro in cell cultures and in experiments on animals. The above methods make it possible to characterize osteointegrative, osteoconductive and osteoinductive properties of biomaterials as well as biodegradation, rather than to reveal only presence or absence of biocompatibility and cytotoxicity of biomaterials, thereby enabling medical specialists to use biomaterials differentially.